Words of Intelligence: An Intelligence Professional's Lexicon for Domestic and Foreign Threats - Goldman, Jan (Rowman & Littlefield Publishers, 2011)
Words of Intelligence: An Intelligence Professional's Lexicon for Domestic and Foreign Threats is intended for the intelligence and national security men and women at the federal, state, and local levels. The intelligence community has undergone massive changes since it developed after World War II. Intelligence work now involves several different processes, including the planning, collection, analysis, and production of information. It also requires extensive expertise in its terminology. And in the post-9/11 era, the intelligence community has expanded, requiring the transmission of information to state and local public administrators, health officials, and transportation planners in times of a possible domestic attack. The number of people who need to know the specialized terminology of the intelligence community continues to grow. This dictionary is an invaluable tool for those requiring a working knowledge of intelligence-related issues from both a foreign intelligence perspective and a local perspective for law enforcement officials. The number of terms, abbreviations, and acronyms has more than doubled for this new edition, and it includes a topical index and extensively cross-referenced entries. This book explains terms that relate to intelligence operations, intelligence strategies, security classifications, obscure names of intelligence boards and organizations, and methodologies used to produce intelligence analysis. Both entry-level and experienced intelligence professionals in the domestic and foreign intelligence communities find this book useful. This book is more than just a reference book; it is a book to read and enjoy, and from which to learn the art and science of intelligence analysis.